ANALISIS FAKTOR â€“ FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA TOKO ONLINE â€œFISHEYE OUTLETâ€ SEMARANG - Kiswuryanto, Reza Pradipta; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2016)
Along with the growth and development of the online store business in Indonesia which has increased very rapidly. The number of online stores offering the product are increasing. Particularly at â€œFisheye Outletâ€ online store that sells gadget accecories and smartphoneaccecories. Increasing competition between online stores to sell their products , causing Fisheye Outlet online store sales decline.Fisheye Outlet online store should be able to use the best marketing strategies to stay afloat.This study uses five variables: quality products, competitive prices, product variety, store image, and purchasing decisions. This research hypothesis testing using the data of 100 respondents. The analysis technique used in this research is to use a software program Statistical Package for Social Science (SPSS) 20.The result of this study indicate that variable product quality positively affect to store image. Then, variable competitive prices, store image, and product variety are positively affect to purchase decision.